PENGARUH LITERASI KEUANGAN DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF SISWA - Theresia Sigiro; Anggun Tiur Ida Sinaga; Herlina Sianipar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of financial literacy and self-control on the consumptive behavior of students at SMA Swasta Kampus Nommensen Pematangsiantar. This research used a quantitative approach with a survey method. The population consisted of 283 students, with a sample of 166 students selected using proportionate stratified random sampling. Data were collected through questionnaires using a Likert scale. The data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination using SPSS. The results showed that financial literacy had a negative and significant effect on students’ consumptive behavior, with a regression coefficient value of -0.362 and a significance value of 0.001 < 0.05. Self-control had a positive and significant effect on students’ consumptive behavior, with a regression coefficient value of 0.333 and a significance value of 0.001 < 0.05. Simultaneously, financial literacy and self-control significantly affected students’ consumptive behavior, as evidenced by the F-test results where Fcount > Ftable and the significance value was 0.000 < 0.05. The multiple linear regression equation obtained was Y = 34,191 – 0.362X1 + 0.333X2. The coefficient of determination (R²) showed that financial literacy and self-control variables were able to explain the influence on students’ consumptive behavior, while the remaining variance was influenced by other variables outside this study. Based on these findings, it can be concluded that financial literacy and self-control influence the consumptive behavior of students at SMA Swasta Kampus Nommensen Pematangsiantar. Therefore, improving financial literacy understanding and self-control abilities is very important in shaping more rational and wise consumption behavior among students.